Literature Review : Kontribusi Parenting Styles Dan Attachment Terhadap Self Disclosure Siswa - Syaddiyah, Halimahtun; F, Firman; N, Netrawati (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Self-disclosure is a crucial aspect in students’ social and emotional development, because it is related to an individual’s ability to express thoughts, feelings, and personal information to others. This study aims to examine the contribution of parenting styles and emotional attachment to students’ self-disclosure. The method used is a literature study with a descriptive qualitative approach. Data were collected from various relevant scientific sources, such as journals, academic books, and scientific articles that discuss the relationship between the main variables. The results of the study indicate that authoritative parenting styles play a positive role in forming open communication and secure attachment, which in turn encourages increased self-disclosure. Conversely, authoritarian and permissive parenting styles tend to create insecure attachments and inhibit self-disclosure. Attachment has been shown to be an important mediator in the relationship between parenting styles and self-disclosure. These findings emphasize the importance of healthy parenting patterns and secure emotional attachments as a foundation for the development of students’ self-disclosure. The implications of this study are relevant to guidance and counseling practices in schools as well as education for parents in supporting children’s psychosocial health.